Analisis Pengaruh Kinerja Perusahaan, Kebijakan Hutang, Ukuran Perusahaan, Dan Nilai Perusahaan Terhadap Tingkat Pengembalian Investasi Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bei Periode 2014-2016 - Julianti Levina Kosman dan Indra Widjaja (Universitas Tarumanagara, 2019)
The purpose of this research is to examine empirically the influence of company performance, debt policy, firm size and firm value toward retun on investment. In this research, researcher used four independent variables and one dependent variabel. Company performance is proxied by Return On Equity (ROE), Debt policy is proxied by Debt to Equity Ratio (DER), firm size is proxied by Natural Logarithm of Total Asset (SIZE), firm value is proxied by Price Book Value (PBV), and return on investment is proxied by Stock Return (RETURN). The sample of the research consist of 36 property and real estate companies listed in Indonesia Stock Exchange in the period 2014-2016. This research used quantitative analysis with panel data estimation methods with time series and cross section data used 5% significance level. The result shows that company performance have a positive effect and insignificant toward stock return, debt policy have a negative effect and significant toward stock return, firm size has a negative effect and insignificant toward stock return and firm value have a positive effect and significant toward the stock return.